MicroRNA-141-3p affected proliferation, chemosensitivity, migration and invasion of colorectal cancer cells by targeting EGFR. (January 2020) - Xing, Yanpeng; Jing, Hongyu; Zhang, Ye; Suo, Jian; Qian, Ming
Highlights: The expression level of miR-141-3p is associated with proliferation of colorectal cancer, migration and invasion. MiR-141-3p plays important role in response to cetuximab treatment. MiR-141-3p could predict the cetuximab sensitivity in colorectal cancer by directly targeting EGFR signaling pathway. Abstract: Colorectal cancer (CRC) is one of the most often diagnosed cancers globally. MicroRNAs are small RNA molecules that play essential roles in tumorigenesis and progression of CRC. Here we evaluated the effects of miR-141-3p on growth, cetuximab sensitivity, migration and invasion of CRC cells. We found that miR-141-3p negatively regulated the proliferation, migration and invasion in CRC cells. In addition, miR-141-3p enhanced the cetuximab sensitivity of CRC cells by EGFR suppression. Moreover, miR-141-3p improved cetuximab-induced apoptosis in CRC cells. Furthermore, miR-141-3p altered the expression of E-cadherin, N-cadherin, snail and Vimentin, indicating miR-141-3p might play a role on epithelial to mesenchymal transition (EMT). Luciferase reporter assay showed that EGFR was the direct binding site of miR-141-3p and the expression levels of p-EGFR, Raf-1, pAKT and p-ERK1/2 were regulated by miR-141-3p. After down-regulation of EGFR by siRNA in CRC cells, the effects of miR-141-3p on proliferation, migration and invasion were reversed. miR-141-3p played important roles in CRC growth and response to cetuximab treatment, and might function as a potential biomarker to predict cetuximab response.